The Tourism Climate Evaluation in Kurdistan Religions Using Environmental Climate Graph (Olgyay) - لوقمان ووسو حسن (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The study area has lots ofpotential tourism particularly those related to climate. This is because of the diversity of topographical features of the area, which mainly consist of both mountains and steppes. Data of (16) weather stations have been analyzed in the research, (10) of them located in the mountainous area, and the other (6) stations located in the steppes, which (62%) and (38%) respectively. In order to achieve the study results the researcher has used Olgyay Chartin the analyzation. It reveals that mountainous area has impact on tourism climate in a way that cools down to uncomfortable temperature during the night and day by percentage of (%36.7) and (30%) respectively, while in the weather station of the steppes area the temperature decreasing recorded as (29%) at night and (25%) during day. Moreover, it shows that the moderate temperature to make feel fully relaxed during night and day in the mountainous area stands between(9.2%), (19.7%), (5.8%) and (25.8%) respectively, at the same time it stands between (1.3%), (16.6%), (6.9% ) and (25%) for the steppes environment. In spite of all of these, the other climatic factors such as wind speed during some warm months and the sun shining in some cold months have affected increasing moderate climate and comfort ratio.